Методика выбора мощности активных фильтрокомпенсирующих устройств - Поднебенная, С. К. (НТУ "ХПИ", 2015)
Одним з важливих питань, що вирішуються при виборі типу активних фільтрокомпенсуючих пристроїв (АФКП), є економічне обґрунтування. Вартість АФКП визначається його потужністю, тому задача правильного її вибору стоїть досить гостро. Повна компенсація потужності спотворень не завжди є економічно обґрунтованою, тому з урахуванням визначень стандарту IEEE 1459–2010 і вимог до параметрів якості електроенергії в точці загального приєднання складено методику, що дозволяє визначити розрахункову потужність АФКП. Для врахування спектрального складу струму нелінійних навантажень потребується введення специфічних обмежень, які дозволяють знизити собівартість АФКП та зменшити втрати потужності в ньому.

One of the important issues which can be solved when choosing the type of active filter-compensating devices (AFCD) is an economic justification. The cost of AFCD is determined by its power rating, so the task of choosing the right AFCD power is quite acute. Full compensation of mains current distortion is not always economically feasible, so, considering the IEEE 1459–2010 standard definitions and requirements for power quality parameters in the point of common coupling, a method of determining the estimated power rating of AFCD is proposed. For taking into account the spectral composition of nonlinear load current, additional specific limitations are required, which allows to optimize the AFCD cost and reduce active power losses in it.
Method of selection of active filter’s power
Keywords: реактивная мощность; силовые активные фильтры; автономный инвертор напряжения; интерфейсный фильтр; точке общего присоединения